History of the Christian church ; v. IV - Schaff, Philip, 1819-1893 (Grand Rapids, MI Eerdmans, 1910)
Contents : v. IV : Mediaeval Christianity from Gregory I to Gregory VII A.D. 590-1073
First published in 7 volumes, 1882-1892. 8 volume set
Keywords: Church history -- Mediaeval church -- 590 - 1073 A.D.